From Gambus to Solo Guitar: Acculturation and Islamic Cultural Identity in Coastal Lampung - Novri Rahman (Journal of Islamic Civilization and Culture Review, 2026)
Despite extensive studies on Islamization, gambus traditions, and musical modernization in Indonesia, limited attention has been given to the integrated historical and ethnomusicological process through which gambus transformed into the Lampung Pesisir solo guitar within the socio-cultural context of the Lampung Saibatin community. This study addresses this gap by examining the transformation of gambus into Lampung Pesisir solo guitar through the interconnected processes of Islamization, cultural adaptation, and modernization. Using a descriptive qualitative approach grounded in ethnomusicological inquiry, data were collected through literature review, participatory observation, in-depth interviews with seven informants, and documentation conducted between 2018 and 2025 in coastal Lampung. The findings reveal that gambus was introduced through Islamic missionary networks and subsequently localized into gambus lunik before undergoing further transformation into gitar tunggal as a creative response to modernization and weakening intergenerational transmission. Rather than representing cultural decline, the emergence of Lampung solo guitar demonstrates a process of adaptive continuity in which Islamic values, communal ethics, and local identity were sustained through changing musical forms. The novelty of this study lies in integrating historical and ethnomusicological perspectives within a layered transformation model (gambus–gambus lunik–solo guitar), while theoretically contributing to discussions of musical creolization and cultural acculturation by showing that modernization may function not only as disruption but also as a mechanism of cultural revitalization and continuity.